Comparison of two clinical scoring systems for emergency department risk stratification of suspected acute coronary syndrome - MacDonald, S.; Nagree, Y.; Fatovich, D.; Flavell, Helen; Loutsky, F. (2011)
Objective: To compare two methods of risk stratification for suspected acute coronary syndrome (ACS) in the ED. Methods: A prospective observational multicentre study was undertaken of patients undergoing evaluation in the ED for possible ACS. We compared the National Heart Foundation of Australia/Cardiac Society of Australia and New Zealand (NHF/CSANZ) guideline and the Thrombolysis in Myocardial Infarction (TIMI) risk score for differentiating high- and low-risk patients. Composite outcome was all cause death, myocardial infarction or coronary revascularisation within 30 days. Results: Of 1758 enrolments, 223 (13%) reached the study outcome. Area under the receiver operator characteristic (ROC) curve was 0.79 (95% CI 0.76-0.81) for the NHF/CSANZ group and 0.71 (0.68-0.75) for TIMI score based on initial troponin result (P<0.001), and 0.82 (95% CI 0.80-0.84) and 0.76 (0.73-0.79) respectively when the 8-12h troponin result is included (P=0.001). Thirty day event rates were 33% for NHF/CSANZ high-risk vs 1.5% for combined low/intermediate risk (P<0.001). For TIMI score, 30 day event rates were 23% for a score =2 and 4.8% for TIMI<2 (P<0.001). The NHF/CSANZ guideline identified more patients as low risk compared with the TIMI risk score (61% vs 48%, P<0.001). Conclusions: The NHF/CSANZ guideline is superior to the TIMI risk score for risk stratification of suspected ACS in the ED. © 2011 The Authors. EMA © 2011 Australasian College for Emergency Medicine and Australasian Society for Emergency Medicine.